Kaji Terap Optimalisasi Pakan Silase Limbah Terubuk Terhadap Jumlah Peningkatan Bobot Sapi - Ali Ramdan Adikara; Cecep Misbahudin (Program Studi Agribisnis, Universitas Muhammadiyah Sukabumi, 2023)
Silage is fermented feed in an ordinary silo or plastic container with an anaerobic process. The purpose of this study was to evaluate the feeding of terubuk silage with green grass on the increase in the weight of cattle in Purabaya District, Sukabumi Regency. The study was carried out as a follow-up to the results of testing in the laboratory. This study used two PO female cows (Ongole breed) or Java cattle aged 6 months and 9 months, which were fed twice a day in the form of crushed silage and were not given any other additional feed. The stages of applied research include the experimental stage or making crushed silage and observation of recording data in the form of recording the growth of cattle weight per week before and after being fed crushed silage. The initial body weight of the cow is the benchmark for this study. The results of the study showed that the feed treated with the most terubuk silage had a better effect on increasing the weight of the cows compared to green grass. Cattle weight has increased to a maximum of 6.15 kg per week or 0.9 kg per day.